Measurement of microparticle tissue factor activity in clinical samples: A summary of two tissue factor-dependent FXa generation assays. Issue 139 (March 2016) - Hisada, Yohei; Alexander, Wyeth; Kasthuri, Raj; Voorhees, Peter; Mobarrez, Fariborz; Taylor, Angela; McNamara, Coleen; Wallen, Hakan; Witkowski, Marco; Key, Nigel S.; Rauch, Ursula; Mackman, Nigel
Abstract: Thrombosis is a leading cause of morbidity and mortality. Detection of a prothrombotic state using biomarkers would be of great benefit to identify patients at risk of thrombosis that would benefit from thromboprophylaxis. Tissue factor (TF) is a highly procoagulant protein that under normal conditions is not present in the blood. However, increased levels of TF in the blood in the form of microparticles (MPs) (also called extracellular vesicles) are observed under various pathological conditions. In this review, we will discuss studies that have measured MP-TF activity in a variety of diseases using two similar FXa generation assay. One of the most robust signals for MP-TF activity (16–26 fold higher than healthy controls) is observed in pancreatic cancer patients with venous thromboembolism. In this case, the TF + MPs appear to be derived from the cancer cells. Surprisingly, cirrhosis and acute liver injury are associated with 17-fold and 38-fold increases in MP-TF activity, respectively. Based on mouse models, we speculate that the TF + MPs are derived from hepatocytes. More modest increases are observed in patients with urinary tract infections (6-fold) and in a human endotoxemia model (9-fold) where monocytes are the likely source of the TF + MPs. Finally, there is no increase in MP-TF activity in the majority of cardiovascular disease patients. These studies indicate that MP-TF activity may be a useful biomarker to identify patients with particular diseases that have an increased risk of thrombosis. Highlights: Functional MP-TF could be a prospective biomarker of a prothrombotic state. The measurement of MP-TF activity in human plasma sample should be standardized. One of the most robust signals for MP-TF is observed in pancreatic cancer with VTE.